2023
DOI: 10.1177/02724316231182297
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Stressors in Early Adolescence: The Role of Educational Track and Ethnic Background

Abstract: The present study aimed to identify overall stress and salient stressors experienced by adolescents from different education tracks and self-perceived ethnic backgrounds. A total of 1489 adolescents ( M = 13.40 years; SD = 0.89 years) from nine Dutch secondary schools participated. Self-reported stressors were measured with the adapted version of the Adolescent Stress Questionnaire – Short. After controlling for age, gender, country of birth, and school classes, results showed that overall stress did not diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Providing A recent systematic review demonstrated that the most salient domains of negative stressors among adolescents are related to the family (e.g., issues with parents), the school (e.g., school pressure), the self (e.g., health issues), and peers (e.g., romantic issues; Núñez-Regueiro & Núñez-Regueiro, 2021). School-related stressors are often experienced by adolescents, and include school pressure (e.g., taking exams, workload), school performance (e.g., keeping up with school work), and academic difficulties (e.g., failure in exams, poor grades; Anniko et al, 2019;Núñez-Regueiro & Núñez-Regueiro, 2021;Vogelaar et al, 2022). For instance, in the Netherlands, one in three secondary students experience stress and pressure from school (Kleinjan et al, 2020;Stevens et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Providing A recent systematic review demonstrated that the most salient domains of negative stressors among adolescents are related to the family (e.g., issues with parents), the school (e.g., school pressure), the self (e.g., health issues), and peers (e.g., romantic issues; Núñez-Regueiro & Núñez-Regueiro, 2021). School-related stressors are often experienced by adolescents, and include school pressure (e.g., taking exams, workload), school performance (e.g., keeping up with school work), and academic difficulties (e.g., failure in exams, poor grades; Anniko et al, 2019;Núñez-Regueiro & Núñez-Regueiro, 2021;Vogelaar et al, 2022). For instance, in the Netherlands, one in three secondary students experience stress and pressure from school (Kleinjan et al, 2020;Stevens et al, 2018).…”
Section: Introductionmentioning
confidence: 99%